Syntactic structure of the verb ir in contemporary european portuguese - Soares, Catarina (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
The aim of this paper is to analyse the syntactic structure of the portuguese verb ir (‘go’). After establishing it as a ditransitive verb, we will proceed to describing its syntactic structure, for which purpose a brief background on X-bar Theory and Theta-Theory will be provided, as they will play crucial roles in our analysis. We will conclude that the syntactic structure of the verb ir is that of a vP-shell.